Hubungan Sosiodemografi dan Kondisi Lingkungan dengan Keberadaan Jentik di Desa Mangunjiwan Kecamatan Demak - Maftukhah, Maftukhah; Azam, Mahalul; Azinar, Muhammad (Universitas Ahmad Dahlan, 2017)
Background: Dengue Hemorrhagic Fever (DHF) is the one of public health problem which transmitted by Aedes Aegypti’s bite. Population density, climate and environmental conditions are the most influential factor. At 2015 DHF had been disease trends in desa Mangunjiwan kecamatan Demak. So, it necessary to refer existence and density’s the vectors. The purpose of this research is to know correlation between sociodemographic and environmental condition with existence larva on desa Mangunjiwan kecamatan Demak. Method: This research is using observational analysis with cross sectional plan. Using random sampling as data collection technique with 100 respondent. The research analysis using univariate and bivariate with Chi Square. Result: Statistical result of the research shows that all of Desa Mangunjiwan’s RW has low population density, the revenue is p=0.799, acidity (pH) is p=0.036, water temperature is p=0.24, air temperature is p=0.616, air humidity is p=0.001. House Index (HI) on Desa Mangunjiwan is 59%, Container Index (CI) is 22%, Breteau Index (BI) is 95% and Larva Free Number (LFN) 41%. Conclusion: The variable that correlated to be larva was environmental condition (acidity, water temperature and air humidity).